Free-Standing Electrospun W-Doped BiVO4 Porous Nanotubes for the Efficient Photoelectrochemical Water Oxidation - Yuan, Xiuhua; Sun, Xia; Zhou, Huawei; Zeng, Suyuan; Liu, Bingxin; Li, Xia; Liu, Dong (Frontiers in Chemistry, 2020)
While bismuth vanadate (BiVO4) has emerged as a promising photoanode in solar water splitting, it still suffers from poor electron-hole separation and electron transport properties. Therefore, the development of BiVO4 nanomaterials that enable performing high charge transfer rate at the interface and lowering charge recombination is urgent needed. Herein, cobalt borate (Co-B) nanoparticle arrays anchored on electrospun W-doped BiVO4 porous nanotubes (BiV0.97W0.03O4) was prepared for photoelectrochemical (PEC) water splitting. One-dimensional, free-standing and porous BiV0.97W0.03O4/Co-B nanotubes was synthesized through electrospun and electrodeposition process. BiV0.97W0.03O4/Co-B arrays exhibit a unique self-supporting core-shell structure with rough porous surface, providing electrochemically active sites exposed to the electrolyte. When applied to PEC water splitting, BiV0.97W0.03O4/Co-B modified FTO electrode displays high incident photon-to-current conversion efficiency (IPCE) of 33% at 405 nm (1.23 V versus RHE) and its photocurrent density is about 4 times to the pristine nanotube. The higher PEC water splitting properties of BiV0.97W0.03O4/Co-B porous nanotubes may be attributed to the effectively suppress the electron-hole recombination at electrolyte interface due to its self-supporting core-shell structure, the high electrocatalytic activity of Co and the good electrical conductivity of BiV0.97W0.03O4 arrays. This work offers a simple preparation strategy for the integrated Co-B nanoparticle with BiV0.97W0.03O4 nanotube, demonstrating the synergistic effect of co-catalysts for PEC water splitting.